Health-related quality of life measured by EQ-5D-3L for the spouses of breast cancer patients - Sun, Li-Fei; Huang, Sheng; Li, Yun-Fen; Yang, Zhuang-Qing; Yang, Xiao-Juan; Zou, Jie-Ya; Wang, Xiao-Wen; Nie, Jian-Yun (Frontiers in Oncology, 2022)
To explore factors influencing the health-related quality of life of spouses of breast cancer patients and the suitable questionnaires for this purpose. A cross-sectional study was conducted in the Third Affiliated Hospital of Kunming Medical University. The spouses of breast cancer patients were included and evaluated via face-to-face interviews. Self-designed demographic characteristics and disease-related questionnaires, the 12-item health survey questionnaire (SF-12), the three-level European five-dimensional health status scale¬¬¬¬ (EQ-5D-3L), and the Social Support Rate Scale (SSRS) were used. The internal consistency reliability measure Cronbach's coefficient, criterion-related validity, construct validity, and sensitivity were used to evaluate the applicability of the EQ-5D-3L. Univariate and multivariate analyses were performed to analyze the factors associated with the health-related quality of life of spouses of breast cancer patients. We investigated a total of 100 spouses of breast cancer patients. Cronbach's α, the internal consistency reliability coefficient, was 0.502. The EQ-5D-3L health utility score was moderately correlated with PCS-12 (r=0.46, p=0.0001) and weakly correlated with MCS-12 (r=0.35, p=0.0001). The EQ-5D-3L health utility score for the spouses of breast cancer patients was 0.870, and the EQ-VAS was 78.3. In multivariate analysis, social support and cognition of the treatment effect were factors that influenced the EQ-5D-3L health utility score. The EQ-5D-3L has good reliability, validity, and sensitivity for measuring the physiological aspects of the health-related quality of life of spouses of BC patients. EQ-5D-3L was considered suitable for this study.